Optimizing the Program to Increase the Use of Domestic Products (P3DN) in Banten Province - Anom, Erman (Jurnal Polisci, 2026)
Background. The Increasing the Use of Domestic Products (P3DN) Program is one of the government's strategic efforts to encourage national economic growth through increasing the absorption of local products. Banten Province as one of the strategic areas in Indonesia has great potential in the development of domestic products, both from the industrial, MSME, and agricultural sectors. Aims. This article aims to analyze the implementation of the P3DN program in Banten Province, the challenges faced, and formulate optimization strategies that can be carried out by local governments and related stakeholders. Method. This study uses a descriptive qualitative approach with literature study methods, document analysis, and limited interviews with MSME actors, local government officials, and industrial estate managers in Banten Province Conclusion. The P3DN program in Banten Province has great potential to be optimized given the abundant industrial and MSME resources. Through a collaborative approach, increased socialization, and facilitation of TKDN certification and local e-catalogs, the implementation of P3DN can run more effectively. Implementation. Local governments need to take an active role as a catalyst for strengthening domestic products to have a positive impact on regional economic growth.